A Mobile-Assisted Peer Assessment Approach for Evidence-Based Nursing Education. Issue 12 (12th December 2021) - Hwang, Gwo-Jen; Wu, Yi-Jung; Chang, Ching-Yi
Abstract : Students who learn evidence-based nursing can assist the healthcare team to make proper medical decisions and provide patients with valuable advice, thus optimizing the quality of patient care in specific situations. In clinical work, nursing staff members participate in decision making by searching for relevant empirical nursing literature, a basic ability required to enter clinical practice. In traditional instruction, nursing students are taught the Problem, Intervention, Comparison, and Outcome method to learn to use library resources and gather empirical nursing knowledge for decision making. However, it is a challenge for most students to have sufficient practice to make decisions correctly and to have opportunities to perceive medical cases from diverse perspectives. Therefore, we propose a peer assessment-based Problem, Intervention, Comparison, and Outcome approach to help nursing students locate correct evidence and make appropriate decisions about patient care. We performed an experiment with our approach in a nursing university training program. The experimental results reveal that the subjects learning with the proposed approach show better evidence-based nursing knowledge, learning attitude, and critical thinking ability than those learning with the traditional approach.